Efficacy of Habit Reversal Training in Children With Chronic Tic Disorders: A Within-Subject Analysis. Issue 1 (January 2020) - Viefhaus, Paula; Feldhausen, Marion; Görtz-Dorten, Anja; Volk, Helene; Döpfner, Manfred; Woitecki, Katrin
The aim of this study is to evaluate a cognitive-behavioral treatment for children and adolescents with tic disorder including habit reversal training (HRT) in a sample of children and adolescents ( n = 27). Multiple outcome measures were used to assess the effects of the treatment on tic symptoms. In addition, impairment/subjective burden ratings and the self-efficacy to control tics were assessed. A within-subject design with two phases (8 weeks diagnostic; 16 sessions treatment) was analyzed using multilevel modeling (MLM). During the treatment phase, significant improvements in tic symptoms, impairment, and self-efficacy to control tics were found on most outcome measures. Treatment effects were found on the clinical rating of tic symptoms ( Yale Global Tic Severity Scale [YGTSS]), the self-efficacy to control tics, and the video-observed motor tic frequency by comparing the improvements during treatment with the course of the outcome measures during the preceding diagnostic phase.